2014
DOI: 10.1021/jp506434a
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Hybrid Photoanodes for Water Splitting by Photodeposition of Iridium Oxide Nanoparticles

Abstract: The efficient coupling between light-harvesting absorbers and cocatalysts allowing for chemical transformation along multielectron pathways is of fundamental importance for the development of solar-fuel-producing photochemical systems. Herein we demonstrate that IrO x nanoparticles acting as efficient cocatalyst for water oxidation can be photoelectrochemically deposited from hexahydroxoiridate solutions into the porous structure of TiO 2 -PH (polyheptazine, "graphitic carbon nitride") hybrid photoanodes for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 91 publications
10
45
1
Order By: Relevance
“…Figure 6 shows the photocurrent response and oxygen evolution of TiO 2 -PH-Co(II) under visible light (λ > 420 nm) irradiation at 1.06 V versus RHE. We note that at relatively low bias potentials (~0.2 V vs. RHE), photocurrents were detectable but very small due to the fast back electron transfer (primary recombination) [29]. A higher bias potential was therefore applied in order to obtain larger photocurrents and detectable amounts of oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 6 shows the photocurrent response and oxygen evolution of TiO 2 -PH-Co(II) under visible light (λ > 420 nm) irradiation at 1.06 V versus RHE. We note that at relatively low bias potentials (~0.2 V vs. RHE), photocurrents were detectable but very small due to the fast back electron transfer (primary recombination) [29]. A higher bias potential was therefore applied in order to obtain larger photocurrents and detectable amounts of oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…We have shown that porous TiO 2 -PH photoanodes loaded with IrO x or CoO x acting as oxygen-evolving cocatalysts are capable of visible 2 O.V. Khavryuchenko et al light-driven oxygen evolution in aqueous electrolytes [22][23][24][25][26]29]. The presence of a cocatalyst was absolutely necessary since no dioxygen evolution is observed at TiO 2 -PH photoanodes without cocatalyst.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…11 In the case of OER, a clear dominant cocatalyst has yet to be established. Several inorganic cocatalysts, such as IrOx, 12 CoOx, 10 Co3O4, 13 NiOx, 9,13 and RuO2, 14 were found to enhance the photocatalytic reaction.…”
Section: Introductionmentioning
confidence: 99%